Mapping the Western Grenville Province: Using Neodymium Isotopic Analysis Accompanied by Spatial Information to Construct a More Accurate Geological Map - Moore, Esther (My University, 2009)
Geochronological study of the Grenville Province has been an ongoing project at McMaster for the past 20 years. Over 1,500 orthogenesis samples have been collected from a 700,000 square kilometer region, and geochemically analyzed for Neodymium model ages. This vast area has been subjected to multiple accretion and ductile deformation episodes, creating great geological complexity.
The two mam belts of the Grenville Province are the Allochthonous Belt, consisting of terranes which were laterally transported by the Grenville orogeny, and the underlying Parautochthonous Belt. The boundary separating these two major belts is termed the Allochthon Boundary Thrust (ABT) and represents the northwesterly limit of major crustal movement during the Grenville orogeny. Due to the high degree of exhumation of mid to lower crustal levels, identification of the ABT is difficult within Southwestern Ontario. As a result, lithological maps, such as the Geological Survey of Canada (GSC) map of the Grenville Province created by Davidson (1998), do not correctly identify sections of the ABT. In addition, impOliant geological features such as structural outliers (klippen) of the Allochthonous belt are not correctly identified. Along much of its length the ABT defines the boundary between Archean- Paleoproterozoic (> 1.8 Ga) and the Paleo- Mesoproterozoic «1.8 Ga) crust. Therefore, by measuring the isotopic composition of either side of the ABT the boundary can be clearly defined.
Previously collected Nd isotope data were plotted on ESRI's Geographical Information System (GIS) and digitally represented. Interpolation based on sample age distribution was conducted to assess completeness of the data set. Interpolation techniques included triangulated irregular networks, inverse distance weighting, and kriging, which were used to obtain global and localized trends. This approach highlighted discrepancies between geological and geospatial interpretation, therefore highlighting areas which needed additional sampling.
Nd-model analysis of olihogneiss from four areas collected within Northeastern Ontario and Southwestern Quebec have provided additional information to this interpolation process. Through the addition of these samples the boundaries of the ABT and klippen have become much more precise. Digital mapping of the terranes of the Grenville Province through integration of the aforementioned techniques has provided an improved understanding to the geological history of the Grenville Orogeny.
Keywords: Earth Sciences; Environmental Sciences; Earth Sciences